2009
DOI: 10.1091/mbc.e09-02-0152
|View full text |Cite
|
Sign up to set email alerts
|

Transportin Regulates Major Mitotic Assembly Events: From Spindle to Nuclear Pore Assembly

Abstract: Mitosis in higher eukaryotes is marked by the sequential assembly of two massive structures: the mitotic spindle and the nucleus. Nuclear assembly itself requires the precise formation of both nuclear membranes and nuclear pore complexes. Previously, importin alpha/beta and RanGTP were shown to act as dueling regulators to ensure that these assembly processes occur only in the vicinity of the mitotic chromosomes. We now find that the distantly related karyopherin, transportin, negatively regulates nuclear enve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 156 publications
7
85
0
2
Order By: Relevance
“…In this process, Importin proteins bind and inhibit factors such as HURP and TPX2, which are essential for microtubule spindle growth, and this inhibition is relieved by Ran-GTP Nachury et al, 2001;Wiese et al, 2001;Silljé et al, 2006). Although these roles have been ascribed for Importin 1 and its Importin- binding partners, Importin 2 might also have a role in mitotic spindle assembly (Lau et al, 2009). In this report and other recent reports, we also suggest a further role for Importin proteins in centrosomal and cilia targeting (Dishinger et al, 2010;Fan et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…In this process, Importin proteins bind and inhibit factors such as HURP and TPX2, which are essential for microtubule spindle growth, and this inhibition is relieved by Ran-GTP Nachury et al, 2001;Wiese et al, 2001;Silljé et al, 2006). Although these roles have been ascribed for Importin 1 and its Importin- binding partners, Importin 2 might also have a role in mitotic spindle assembly (Lau et al, 2009). In this report and other recent reports, we also suggest a further role for Importin proteins in centrosomal and cilia targeting (Dishinger et al, 2010;Fan et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…In Figure 4C, we probed for the presence of ELYS in our Nup107-160 immunoprecipitation to compare to published reports. [25][26][27] We found ELYS at 6 h and 9 h time points corresponding to S phase transition and the onset of mitosis (Fig. 4C).…”
Section: Resultsmentioning
confidence: 79%
“…[19][20][21][22][23][24] An additional non-Nup member may be ELYS, a putative transcription factor, which was also discovered to copurify with the Nup107-160 complex in Xenopus interphase extracts, Xenopus mitotic extracts and human cell extracts. [25][26][27] Positioned at the curvatures of the membrane embedding the NPC, the Nup107-160 subcomplex acts to stabilize these bends in the membrane. 28 This subcomplex has been classified as a keystone of NPC assembly and is required for assembly of a subset of Nups into the NPC.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that importin-b negatively regulates several distinct steps in postmitotic NPC assembly, including chromatin seeding by ELYS-Nup107-160 (Harel et al, 2003a;Lau et al, 2009;Rotem et al, 2009;Walther et al, 2003). We next investigated whether importin-b was also capable of regulating the binding of POM121 DN to chromatin.…”
Section: Importin-b Negatively Regulates the Chromatin Binding Determmentioning
confidence: 99%